Strategy for Improving the ‎Competency of Islamic Religious ‎Education Teachers Through a ‎Continuous Professional ‎Development Program - Zulkifli Maulana Fikran; Fahmi Hanifa (el-Tarbawi : Jurnal Pendidikan Agama Islam, 2025)
This study aims to identify and analyze effective strategies for improving the competency of Islamic Religious Education (PAI) teachers through a continuous professional development program. PAI teacher competency is crucial in shaping the character and religious values ​​of students. However, there are still challenges in implementing appropriate programs to improve these competencies, especially in an era of rapid change and the needs of 21st- century education. This study used a qualitative approach with a case study method in several secondary schools that have implemented professional development programs. Data were collected through in-depth interviews, observation, and documentation, which were then analyzed thematically. The results showed that effective competency development strategies encompass several key aspects, namely: technology-based training, collaboration between teachers, coaching through academic supervision, and providing constructive feedback. In addition, the involvement of school principals and education supervisors plays a significant role in creating an environment that supports continuous learning for PAI teachers. A planned and structured continuous professional development program can improve PAI teachers' understanding of innovative learning methods and their ability to face challenges in the classroom. The conclusion of this study emphasizes the importance of implementing systematic and sustainable strategies to improve PAI teacher competency in order to achieve better educational goals.